DEMOCRACY, ELECTORAL PROPAGANDA AND DATA PROTECTION (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2012)
The paper deals with the right and secret vote with equal value for all, which is even one of the facets of citizenship, a civic duty, the result of social achievements and rights acquired by the people. Moreover, the elections of the representatives are indispensable to the guarantee of a free vote and the maintenance of the democratic order of the rule of law. In this scenario, electoral propaganda plays an important role in the legitimacy of the electoral process and indirectly of citizenship itself. However, given the recent growth ofelectionadvertising on the Internet  and the risks of the processing of users' personal  data, for manipulation dissemination of electoral political content that undermine stake in the right conditions between candidates, harming democracy. In the end, the legal principles of data protection stand out, as an instrument for regulating the processing of data for political purposes, which guarantees better electoral dispute and prestigious citizenship and democracy.